# How do you solve # - 4( 2x - 1) = - 6( x + 2) - 2#?

##### 2 Answers

#### Answer:

#### Explanation:

We need to distribute the

We can simplify the right side to get

I want my variables on the left and the constants on the right. So let's start by subtracting

Let's add

Dividing both sides by

Hope this helps!

#### Answer:

#### Explanation:

#"distribute brackets on both sides of the equation"#

#-8x+4=-6x-12-2#

#"add "6x" to both sides"#

#-8x+6x+4=-14#

#"subtract 4 from both sides"#

#-2x=-14-4=-18#

#"divide both sides by "-2#

#(cancel(-2) x)/cancel(-2)=(-18)/(-2)rArrx=9#

#color(blue)"As a check"# Substitute this value into the equation and if both sides are equal then it is the solution.

#"left "=-4(18-1)=-4xx17=-68#

#"right "=-6(9+2)-2=-66-2=-68#

#x=9" is the solution"#